(untitled) (LEGAL DIALOGICA, 2025)
This research aims to find out and analyze the legal provisions that govern financing for the appointment of third parties. As well as to find out and analyze the form of accountability of the finance company for the actions of third parties who forcibly withdraw the debtor’s assets. This research is a type of normative legal research that is legal research that is carried out by researching literature materials or legal materials by taking issues from law as a norm system used, normative legal research makes the norm system the center of study. The results of this study show that the legal provisions governing the financing of the appointment of third parties affirm that third parties (such as debt collectors) can only act on the basis of a valid agreement and must not act unilaterally. This is regulated in the Constitutional Court Decision Number 18/PUU-XVII/2019 and is supported by provisions in the Civil Code and the Consumer Protection Law, which emphasizes the protection of debtors’ rights and the need for agreement and approval in the implementation of collection or execution of guarantees. And the form of accountability of the finance company for the actions of the collector who forcibly withdraws the debtor’s assets, namely: civil (Article 1365 of the Civil Code), contractual (default), administrative (violation of OJK provisions), and business morals and ethics (through GCG and CSR principles). This responsibility affirms the company’s obligation to ensure the entire collection process is in accordance with the law and respects the rights of the debtor. Abstrak: Penelitian ini bertujuan Untuk mengetahui dan menganalisis ketentuan hukum yang mengatur pembiayaan atas penunjukan pihak ketiga. Serta untuk mengetahui dan menganalisis bentuk pertanggungjawaban perusahaan pembiayaan terhadap tindakan pihak ketiga yang melakukan penarikan paksa aset debitur. Penelitian ini ialah jenis penelitian hukum normatif merupakan penelitian hukum yang dilakukan dengan cara meneliti bahan pustaka atau Bahan Hukum dengan mengambil isu dari hukum sebagai sistem norma yang digunakan maka penelitian hukum normatif menjadikan sistem norma sebagai pusat kajian. Hasil penelitian ini menunjukkan bahwa Ketentuan hukum yang mengatur pembiayaan atas penunjukan pihak ketiga menegaskan bahwa pihak ketiga (seperti debt collector) hanya dapat bertindak berdasarkan perjanjian yang sah dan tidak boleh melakukan tindakan sepihak. Hal ini diatur dalam Putusan Mahkamah Konstitusi Nomor 18/PUU-XVII/2019 serta didukung oleh ketentuan dalam KUH Perdata dan Undang-Undang Perlindungan Konsumen, yang menekankan perlindungan hak-hak debitur dan keharusan adanya kesepakatan serta persetujuan dalam pelaksanaan penagihan atau eksekusi jaminan. Dan bentuk pertanggungjawaban perusahaan pembiayaan terhadap tindakan juru tagih yang melakukan penarikan paksa aset debitur, yaitu: perdata (Pasal 1365 KUH Perdata), kontraktual (wanprestasi), administratif (pelanggaran terhadap ketentuan OJK), serta moral dan etika usaha (melalui prinsip GCG dan CSR). Tanggung jawab ini menegaskan kewajiban perusahaan untuk memastikan seluruh proses penagihan sesuai hukum dan menghormati hak debitur.